Fast and Stable Scanning Technology for a Rotating Dual Grating Based on Inertial Navigation Feedforward and Fuzzy PID Control for Shipborne Platforms - Wang Xi; Yang Liu; Yunjie Teng; Qiran Wang; Hengjie Wang; Fujing Zhang; Fengshou Shi; Xinqing Yi (Journal of Marine Science and Engineering)
To achieve fast and stable scanning on lightweight shipborne electro-optical platforms, we propose a rotating dual-grating two-dimensional scanning system with inertial navigation feedforward and Fuzzy PID control. First, a two-dimensional scanning model using rotating dual grating with inertial navigation feedforward technology was proposed; in that system, the required positional information for the two gratings is determined based on the target location data. Then, the scanning model was combined with the Fuzzy PID algorithm to design a servo system controller that controls the dual gratings to perform beam deflection and scanning, then simulation. Finally, an experimental platform was built for validation. Under a sea-surface disturbance of 10° at 0.1 Hz, the scanning error of the entire process was controlled within 0.328 mrad (RMS) and the scanning of a 15° (half-angle) circular region was completed within 28 s. Compared with traditional control systems, significant improvements were achieved, with the scanning accuracy increased by more than 40.85% and the scanning speed improved by over 21.42%. This paper provides a reference for the application of a rotating dual grating electro-optical scanning platform on shipborne platforms.